Effects of defatted dried roselle (Hibiscus sabdariffa L.) seed powder on lipid profiles of hypercholesterolemia rats. - Khairul Ikram, Emmy Hainida; Ismail, Amin; Hashim, Normah; Mohd Esa, Norhaizan; Abu Bakar, Ainul Zakiah (Wiley-Blackwell, 2008)
BACKGROUND: In vivo investigations were made of the effect of defatted dried roselle seed powder (DRS) on the lipid profiles of rats with induced hypercholesterolemia. The two-batch sample consisted of 23 and 20 Sprague-Dawley male rats randomly divided into four groups and fed with four different diets. The first batch of rats was fed with normal, hypercholesterol, hypercholesterol + 10 g kg-1 (w/w) DRS and hypercholesterol + 20 g kg-1 (w/w) DRS diets. The second batch of rats was fed with normal, hypercholesterol, hypercholesterol + 50 g kg-1 (w/w) DRS and hypercholesterol + 150 g kg-1 (w/w) DRS diets. Treatments were given for a total of 5 weeks.